Comparison of Elaeagnus angustifolia Extract and Sildenafil Citrate on Female Orgasmic Disorders: A Randomized Clinical Trial - M Akbarzadeh; S Zeinalzadeh; J Zolghadri; A Mohagheghzadeh; P Faridi; S Sayadi (JRI, 2014)
Background: Orgasmic disorder can create a feeling of deprivation and failure and provide mental problems, incompatibility and marital discord. This study aimed to compare the effects of Elaeagnus angustifolia flower extract and sildenafil citrate on female orgasmic disorder in women in 2013. Methods: In this randomized clinical trial, 125 women between 18-40 years old who suffered from orgasmic disorder were divided into three E. angustifolia, sildenafil citrate and control groups. The data were gathered using Female Sexual Function Index and through measurement of TSH and prolactin. The first intervention group had to consume 4.5 gr E. angustifolia extract in two divided doses for 35 days and the second one had to use 50 mg sildenafil citrate tablets for 4 weeks one hour before their sexual relationship. However, the control group had to consume the placebo. The data were analyzed using paired t-test, one-way ANOVA, and Bonferroni post-hoc test and p<0.05 was considered significant. Results: The frequency of orgasmic disorder before the intervention was 41.5%, 40.5%, and 57.1% in E. angustifolia, sildenafil citrate, and control groups, respectively (p=0.23). However, these measures were respectively 29.3%, 16.7%, and 50% after the intervention (p=0.004). A significant difference between the two groups regarding sexual satisfaction after the intervention (p=0.003) compared to the beginning of the study (p=0.356). Besides, the highest reduction of changes after the intervention (58.82%) was observed in the sildenafil citrate group. Conclusion: Both E. angustifolia extract and sildenafil citrate were effective in reduction of the frequency of orgasmic disorder in women.